2020
DOI: 10.11648/j.sjac.20200804.11
|View full text |Cite
|
Sign up to set email alerts
|

Effects of <i>Moringa oleifera</i> Biochemical Constituents on Kidney, Liver and Brain of Wister Rats

Abstract: Medicinal plant have evolved over the centuries as essential parts of African civilization and are widely recognized today as representing its rich cultural and scientific heritage. The increasing demand for Medicinal plant products has renewed interest in the pharmaceutical industry in the production of herbal health care formulations, herbal-based cosmetic products, and herbal nutritional supplements. Thus, in addition to serving medical and cultural functions, Medicinal plants in Africa have economic import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…powerful antioxidant effect of Moringa oleifera, This study was aimed at determining changes in as reported by (Hassan et al, 2020). Moreover, testosterone levels of Wistar rats exposed to petrol, (Oa et al, 2017) illustrated that the presence of diesel and kerosene and the ameliorative effect of flavonoids in Moringa oleifera leaf extract has a Moringa oleifera leaf extract on the rats.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…powerful antioxidant effect of Moringa oleifera, This study was aimed at determining changes in as reported by (Hassan et al, 2020). Moreover, testosterone levels of Wistar rats exposed to petrol, (Oa et al, 2017) illustrated that the presence of diesel and kerosene and the ameliorative effect of flavonoids in Moringa oleifera leaf extract has a Moringa oleifera leaf extract on the rats.…”
Section: Discussionmentioning
confidence: 96%
“…A lot of above the sea level (Nata, 2009). The state shares publications have reported some of the specific effects common borders with Niger Republic to the of Moringa oleifera leaf extract on some body tissues North, Kebbi State to the South and Zamfara or organs (Hassan et al, 2020). It has an impressive…”
mentioning
confidence: 99%
“…MO is also a rich source of a wide range of phytochemicals, which, when purified, each have their own unique medicinal properties [ 13 ]. Whilst its phytochemistry is has been largely investigating for managing diseases like diabetes mellitus and hypertension [ 14 ], recent studies have suggested that MO's derivatives may act as promising neuroprotective agents against ischemic stroke but reducing the oxidative stress [ [15] , [16] , [17] , [18] ] ( Fig. 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…
Fig. 1 Hypothesised effect of Moringa oleifera on the ischemic cascade [ [15] , [16] , [17] , [18] ]. Created witg BioRender.com.
…”
Section: Introductionmentioning
confidence: 99%